TINJAUAN DAMPAK BANJIR LAHAR KALI PUTIH, KABUPATEN MAGELANG PASCA ERUPSI MERAPI 2010 - Aisyah, Nur; Purnamawati, Dwi Indah (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
Potency of Merapi lahars in Putih River, Magelang Regency, is described in terms of management of material deposition. The methode is carried out with the description of material, determination of lahars forming factors, and the geology environmental. Merapi eruption on 2010 has producted volcanic materials about 130 million metre cubic, spread in the upper river of Merapi Volcano as Gendol River, Apu River, Trising River, Senowo River, Lamat River, Putih River, Bebeng River, Krasak River, Bedog River, Boyong River, Kuning River, Opak River and Woro River. One of the rivers in Magelang regency known Putih River, has material volcanic as much as 8,2 million metre cubic. Lahars which to is grouped materials clasification like sands and rocks varying in size. While impact of lahars which must to beware are debris avalanche, over topping, and flood. Therefore in order to minimize the abuse authority, disaster management covers prevention, emergency response, and rehabilitation after disaster is necessary.